If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+7=3(x-1)
We move all terms to the left:
7x+7-(3(x-1))=0
We calculate terms in parentheses: -(3(x-1)), so:We get rid of parentheses
3(x-1)
We multiply parentheses
3x-3
Back to the equation:
-(3x-3)
7x-3x+3+7=0
We add all the numbers together, and all the variables
4x+10=0
We move all terms containing x to the left, all other terms to the right
4x=-10
x=-10/4
x=-2+1/2
| h8= 6 | | -5(x+1)=-7x+15 | | 19s-16s=-12 | | 9w-29=-7(w-5) | | 0.08x+8.3=6.14 | | 3.25=1/x-1.2 | | 8x+x-9x+x=17 | | b=7/6 | | 5(v-5)=-3-33 | | 6y-7-3y+3=0 | | 7a-3=3=3-2a | | 4^(3x-2)=5 | | 12s+s-13s+3s+3s=18 | | -40=13t | | -6u-22=-2(u+5) | | 20x-3=36+9 | | -8=-4k | | 12s+s-s13s+3s+3s=18 | | (x+5)=(5x-27) | | 3/4x+6=26-(1/2x+10) | | 3(-2x+4)=-4(2x-6) | | 6(y+2)=-48 | | 2x+x=5=-3x-5x=3 | | 10+3x=25+1x | | 7x+38=-6(5-4x) | | 1/5(-15w-20)+1/2(3-4=) | | 7x+2-3x=10-2x+4 | | -6-3m=-5m+6 | | 3x+15=2x-3x=-17 | | -17.2(82u-86)=-154.8(6u-22) | | (5y-5)-(9y-1)=-4y-4 | | 8(8x+7)=-8(x+2) |